On the optimum mesh size for the capture of Barbus tor (Hamilton) - Kesavan Nair, A.K., Khan, A.A., George, N.A., Mathai, T.J. and (Fishery Technology, 2021)
Results of mesh selectivity experiments on B. tor are presented in this paper. Selectivity curve on the basis of maximum girth of fish in relation to perimeter of mesh was worked out. The optimum girth/mesh perimeter ratio was found to be 1.31. A linear regression of G+0.445L=12.8 was fitted for conversion of length to girth.